Field notes and Beth Proescholdt letter, fall 1991 - Proescholdt, Bethet al (1991)
The field notes consist of the different species of hawks sighted at Grammer Grove County Wildlife Area from September 11, 1991 to November 4, 1991. Included with the field notes is a letter from Beth Proescholdt describing the location and weather conditions. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1991. Epson - sheet feed